Analysis of the stress state of rocks transformation near a horizontal well during acid treatment based on numerical simulation - Sergei N. Popov; Sergei E. Chernyshov; Xiaopu Wang (Записки Горного института)
The article presents an overview of the assessment and modelling of the stress state of rocks in the near-wellbore zone of horizontal wells during acid stimulation of the formation for improving the efficiency of oil and gas field development. A numerical finite element model of near-wellbore zone of the reservoir drilled by a horizontal section was compiled using one of oil fields in the Perm Territory as an example. The distribution of physical and mechanical properties of the terrigenous reservoir near the well was determined considering transformation under the action of mud acid for different time periods of its injection. Multivariate numerical simulation was performed and the distribution of horizontal and vertical stresses in near-wellbore zone was determined with regard for different values ​​of pressure drawdown and changes in stress-strain properties depending on the area of ​​mud acid infiltration. It was found that a change in elastic modulus and Poisson's ratio under the influence of acid led to a decrease in stresses in near-wellbore zone. Analysis of the stress distribution field based on the Coulomb – Mohr criterion showed that the minimum safety factor of rock even after the effect of mud acid was 1.5; thus, under the considered conditions of horizontal well modelling, the reservoir rock remained stable, and no zones of rock destruction appeared.